Quantification of isonicotinoyl lactosyl hydrazone in oral pharmaceutical dosage forms. Issue 3 (2009) - Córdoba-Díaz Córdoba-Díaz, D. D.; Córdoba-Díaz Córdoba-Díaz, M. M.; Elorza Elorza, B. B.
Abstract : Isoniazid, one of the most important drugs for the chemotherapy of tuberculosis, can react with some widely used pharmaceutical excipients, like lactose, leading to the formation of hydrazones. This interaction can dramatically modify the oral bioavailability of the drug, what could lead to a failure of the treatment. Some analytical methods, including techniques like HPLC, can be used to quantify this type of products, but all of them are tedious and time-consuming. In this sense, the aim of the present work is to develop a sensitive, rapid and cheap alternative to other published methods. For this reason, two spectrophotometric methods were developed and validated. In the first one, isoniazid and its lactosyl-hydrazone were measured together. The second one involved a reaction between not bound to lactose isoniazid and 2, 3-dichloro-1, 4-naphthoquinone. Lactosyl-hydrazone is quantified by comparison of the results obtained from both methods. The linearity is confirmed to be within a range of 1.5–30.0 μg/ml of total isoniazid and 0.5–30.0 μg/ml of "free" isoniazid. Limits of quantification of 1.2 μg/ml and 0.3 μg/ml were obtained for bound and free isoniazid respectively. These results indicated that the here described methods are at least, as sensitive and accurate as the vast majority of the previously published chromatographic methods. This methodology shows a good repeatability (RSD below 2.0%) as well as good accuracy (average recoveries of 100.83% and 99.96% for total and free isoniazid respectively). The results obtained from the assay of isoniazid tablets demonstrated that the proposed method constitutes a clear alternative to chromatographic methods and also to the official titration method. It would be of interest for the routine quality control of oral dosage forms containing isoniazid and lactose and for stability studies.